The Effectiveness of Group Identification on Women Economic Empowerment: A Case of the Project to Empower Women through Savings and Loan Associations (PEWOSA) - Nakimuli, Leticia; Ntayi, Joseph; Sajjabi, Florence Bakibinga; Kizza, James (East African Journal of Business and Economics, 2024)
The purpose of the study was to investigate whether identification with a women's group had helped women achieve economic empowerment. The study was underpinned by the social identity and economic empowerment theories and adopted a mixed methods approach. The quantitative data was collected using 360 questionnaires that were given to women while qualitative data was collected from 21 key informants and 20 focus groups. The quantitative data analysis involved descriptive statistics and Structural Equation Modeling using SMART PLS Version 4 while qualitative data was analysed using NVIVO software. The study findings supported the tenets of social identity theory. In this, the constructs of group identity, that is, group centrality, in-group affect and in-group ties did positively influence economic empowerment. However, the association between centrality and financial autonomy, centrality and economic security, in-group ties and decision-making were not supported. It is recommended that Promoters of these groups promote transparent and fair leadership, group leaders adhere to principles of transparency, fairness, and inclusivity. Any form of perceived favouritism be managed in time to foster trust and positive emotional attachment within the group